Access the Quality Service of Ganeshman Singh Memorial Hospital and Research Center - Gurung, Milan; Thapa, Narayan; Khadka, Milan; Karki, Tej Bahadur; Neupane, Dasarath (Nepal Journal of Multidisciplinary Research, 2020)
The aim of this paper is to assess the quality of services in the Ganeshman Singh Memorial Hospital and Research Center, Lalitpur, Nepal, considering that the quality is a key parameter in performance evaluation. Patients are the main actors in evaluating and judging the quality, therefore this study is based on a questionnaire completed by 53 patients and visitors between January and February, 2020. The results show that services by the paramedical staff (OPD nurses) have the highest mean value (mean = 4.17) which is closed to the excellent performance of hospital whereas the lowest mean was 3.57 rated for the cleanliness of the hospital, including the reception area, OPD and surrounding area. Though, in average (mean = 3.77), facilities of Hospital were rated as ‘Good’ in total. Similarly, the cost of medicine was slightly expensive in comparison of other cost like consultation fee, cost of diagnosis and lab test and registration. The patients had rated the cost of hospital in totality as ‘Good’ status, which indicates that the total cost of treatment was affordable for the patient. With the necessary inputs from the patients and the attendants by pointing various drawbacks or deficiencies should always be taken care of by the hospital administration that will turn into a good result of improvement in the hospital services to the satisfaction of the patients.